A Review of Physiological and Biomechanical Injuries in Wrestling - Amir Hossein Hormati; Ebrahim Piri; Amir Ali Jafarnezhadgero (Biyumikānīk-i varzishī, 2023)
Objective Wrestling is one of the sports that have a high percentage of injuries. Therefore, the aim of this study was to review physiological and biomechanical injuries in the field of wrestling. Methods The present study was a library-based and systematic review. The search for articles in Persian and Latin was conducted from 2010 to 2022. This search was performed across different databases, including WOS, SID, Magiran, Scopus, PubMed, ISC, and Google Scholar. Fifty-five relevant articles were selected based on inclusion and exclusion criteria. Finally, 12 articles related to the review of physiological and biomechanical injuries in the field of wrestling were analyzed. Results The findings showed that the average injuries in the lower area were about 34%, and in the upper area, it was 33%. In the lower part, most of the injuries were reported in the knee and ankle joints, and in the upper part, they were reported in the shoulder, elbow, and waist joints. Conclusion It seems that excessive weight loss, along with non-observance of the principles of warming up and cooling down in the field of wrestling, is of great importance in the occurrence of injuries in this field.